2012
DOI: 10.1037/a0024510
|View full text |Cite
|
Sign up to set email alerts
|

Memory inhibition, aging, and the executive deficit hypothesis.

Abstract: Although memory inhibition seems to underlie retrieval-induced forgetting (RIF), there is some controversy about the precise nature of this effect. Because normal RIF is observed in people with deficits in executive control (i.e., older adults), some have proposed that an automatic-like inhibitory process is responsible for the effect. On the contrary, neurocognitive and dual-task findings with young people support the view that an executive control process underlies RIF. In the present study, we address this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
67
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 59 publications
12
67
1
3
Order By: Relevance
“…Second, inhibition is unlikely to be an all-or-none resource. In fact, in their recent work, Ortega, Gómez-Ariza, Román, and Bajo (2012) found that healthy older adults exhibit normal levels of retrievalinduced forgetting when retrieval practice is undertaken under typical conditions, but significantly less retrievalinduced forgetting when retrieval practice is undertaken concurrently with a task that taxes executive control. This finding suggests that the consequences of inhibitory deficits for retrieval-induced forgetting may only become apparent when they are great enough to impede the successful inhibition of competing responses.…”
Section: Trajectorymentioning
confidence: 99%
See 1 more Smart Citation
“…Second, inhibition is unlikely to be an all-or-none resource. In fact, in their recent work, Ortega, Gómez-Ariza, Román, and Bajo (2012) found that healthy older adults exhibit normal levels of retrievalinduced forgetting when retrieval practice is undertaken under typical conditions, but significantly less retrievalinduced forgetting when retrieval practice is undertaken concurrently with a task that taxes executive control. This finding suggests that the consequences of inhibitory deficits for retrieval-induced forgetting may only become apparent when they are great enough to impede the successful inhibition of competing responses.…”
Section: Trajectorymentioning
confidence: 99%
“…For example, when a subset of items are re-presented for additional study instead of retrieval practice, this extra study results in comparable strengthening of target items but typically fails to cause nonstrengthened items to be forgotten (e.g., Anderson et al 2000a;Bäuml, 2002;Ciranni & Shimamura, 1999;Saunders et al, 2009). Similarly, a variety of manipulations-including dividing attention (Ortega, Gómez-Ariza, Román, & Bajo, 2012;Román, Soriano, Gómez-Ariza, & Bajo, 2009), inducing stress (Koessler, Engler, Riether, & Kissler, 2009), inducing negative mood (Bäuml & Kuhbandner, 2007), and reexposing items between retrieval practice and the final test (Storm et al, 2008)-selectively disrupt retrieval-induced forgetting without influencing the strengthening of practiced items. These and other observations have shown that retrievalinduced forgetting can be selectively diminished while preserving both retrieval-practice performance and the strengthening of Rp+ items.…”
Section: Trajectorymentioning
confidence: 99%
“…Evidence from experimental studies has suggested that inhibitory executive control is involved in the retrieval of information from long-term memory (Levy & Anderson, 2008;Ortega, Gómez-Ariza, Román, & Bajo, 2012;Román, Soriano, Gómez-Ariza, & Bajo, 2009). Inhibition in memory selection has been studied via the retrieval practice (RP) paradigm (Anderson, R. A. Bjork, & E. L. Bjork, 1994), a procedure in which participants first study cue-item pairs wherein each cue is associated with several items (e.g., fruit-banana, fruit-kiwi, tool-hammer, tool-pliers).…”
mentioning
confidence: 99%
“…For instance, it seems that the effect is maintained in early aging, but disappears during late aging (Aslan & Bäuml, 2012;Marful, Gómez-Amado, Ferreira, & Bajo, in press). Moreover, early aging participants' ability to inhibit competing items seems to disappear when their memory capacities are overloaded, by introducing, for instance, a dual task (Ortega et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Note that the term "controlled mechanism" does not necessarily involve intentionality. Instead, the term implies that executive control processes underlie the effects found in this paradigm and in fact, many recent studies speak in favor of this assumption (e.g., Román, Soriano, Gómez-Ariza, & Bajo, 2010;Ortega, Gómez-Ariza, Román, & Bajo, 2012).…”
Section: Introductionmentioning
confidence: 95%